2021
DOI: 10.1080/23311975.2021.1930499
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of over-indebtedness among microfinance institutions’ borrowers: The Tanzanian perspective

Abstract: The introduction of microfinance institutions is viewed as the best alternative source of financial services for low-income earners as a means to raise their income and reduce poverty. However, empirical research has indicated that the majority of microfinance institutions' borrowers are over-indebted. Overindebtedness has negative consequences for debtors, creditors, and for the economy as a whole. Since over-indebtedness is a context-specific phenomenon, it lacks universally accepted indicators. This study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
0
5
0
2
Order By: Relevance
“…Governance and Consumer Issues of Bank X and Bank Y According to Kasoga & Tegambwage (2021), policymakers are advised to reschedule loan payments and reduce the number of large loans. This research is also related to the achievement of SDG 8, namely sustainable and inclusive economic growth and ISO 26000 Core Subject Consumer Issues related to customer service, data protection, and customer privacy that can increase corporate value and investor trust by implementing sustainable governance practices.…”
Section: Resultsmentioning
confidence: 99%
“…Governance and Consumer Issues of Bank X and Bank Y According to Kasoga & Tegambwage (2021), policymakers are advised to reschedule loan payments and reduce the number of large loans. This research is also related to the achievement of SDG 8, namely sustainable and inclusive economic growth and ISO 26000 Core Subject Consumer Issues related to customer service, data protection, and customer privacy that can increase corporate value and investor trust by implementing sustainable governance practices.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the percentage of families with children exceeded 50%, with 90% of them having no more than two children. For comparison, in the research sample analysed by less than 40% had dependent children; in a study focused on China (Deng & Yu, 2021) the average number of children was less than one, whereas the research by Kasoga and Tegambwage (2021) reported that the majority of families had three or more children. Second, the employed dataset misses some information due to the strictly limited length of survey questionnaire.…”
Section: Conclusion Limitations and Future Research Directionsmentioning
confidence: 95%
“…When considering the relationship between children and debt, it is important to pay attention to the broader context. Problems with debt are not limited to financial matters but have also a psychological dimension (Kasoga & Tegambwage, 2021;Lea, 2021). The psychological debt burden is usually investigated by referring to the household's appraisals of their financial situation and perception of repayments, so it is subjective (Betti et al, 2007;D'Alessio & Iezzi, 2016).…”
Section: Literature Review: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Jika pendapatan seseorang yang dihasilkan lebih kecil dari kebutuhannya maka seseorang akan melakukan utang demi memenuhi kehidupannya. Hal ini dapat menyebabkan seseorang terpaksa harus memenuhi kebutuhan hidupnya dengan berhutang (Kasoga & Tegambwage, 2021). Jumlah tanggungan juga dapat memoderasi pengaruh orientasi menabung terhadap kecenderungan berhutang.…”
Section: Pendahuluanunclassified